IMPLEMENTATION OF ARABIC-LISTENING SPEAKING MEDIA IN TEACHING LISTENING SKILLS FROM THE PERSPECTIVE OF STEPHEN KRASHEN’S THEORY - Oktari, Sri Jomila; Abidin, Munirul; Yurisa, Penny Respati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Arabic language learning at the junior high school level plays an important role in developing students’ foundational language competencies, particularly listening skills as the basis for speaking skills. However, instructional practices are still largely dominated by text-based methods, resulting in limited authentic oral exposure and causing students to experience difficulties in understanding spoken Arabic. This study aims to describe the implementation of Arabic-Listening Speaking media in teaching listening skills at SMP Muhammadiyah 06 Dau Malang, based on Stephen Krashen’s Second Language Acquisition Theory, specifically the Input Hypothesis and the Affective Filter Hypothesis. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and documentation, and were analyzed using the Miles, Huberman, and Saldana model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the systematic use of audio media, interactive videos, and applications through the stages of pre-listening, whilst-listening, and post-listening provides authentic and contextual input in accordance with the i+1 principle. The media enhance vocabulary mastery, intonation, and sentence structure, while also fostering students’ motivation, participation, and self-confidence. Repetition, scaffolding, and collaborative strategies effectively address learning barriers, demonstrating that the media optimally support the improvement of listening skills. Keywords: Media Arabic-Listening Speaking, Listening Skills, Language Acquisition, Stephen Krashen ABSTRAK Pembelajaran bahasa Arab di tingkat tingkat sekolah menengah pertama memiliki peran penting dalam membangun kompetensi dasar berbahasa, khususnya keterampilan mendengar sebagai fondasi keterampilan berbicara. Namun, praktik pembelajaran masih didominasi metode tekstual sehingga paparan lisan autentik terbatas dan siswa mengalami kesulitan memahami bahasa Arab lisan. Penelitian ini bertujuan mendeskripsikan implementasi media Arabic-Listening Speaking dalam pembelajaran keterampilan mendengar di SMP Muhammadiyah 06 Dau Malang berdasarkan teori pemerolehan bahasa kedua Stephen Krashen, khususnya Input Hypothesis dan Affective Filter Hypothesis. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, serta dokumentasi, kemudian dianalisis dengan model Miles, Huberman, dan Saldana melalui tahap reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan media audio, video interaktif, dan aplikasi secara sistematis melalui tahap pre-listening, whilst-listening, dan post-listening mampu menyediakan input yang autentik, kontekstual, dan sesuai prinsip i+1. Media ini meningkatkan penguasaan kosakata, intonasi, dan struktur kalimat, serta mendorong motivasi, partisipasi, dan kepercayaan diri siswa. Strategi pengulangan, scaffolding, dan kolaborasi efektif mengatasi hambatan pembelajaran, sehingga media terbukti mendukung peningkatan keterampilan mendengar secara optimal. Kata kunci: Media Arabic-Listening Speaking, Keterampilan Mendengar, Pemerolehan Bahasa, Stephen Krashen